Advancing Library Services for Mobile Users - Liu, Yan Quan (IGI Global Scientific Publishing, 2025)
As mobile technology becomes integral to everyday life, libraries rework their services to meet the needs of their users. Advancing library services for mobile users requires seamless, intuitive experiences that support research, learning, and engagement. From mobile-friendly catalogs and e-book pla...
Keywords: dept.ils